Borehole Volumetric Strainmeter Calibration From a Nearby Seismic Broadband Array at Etna Volcano. Issue 10 (21st October 2017) - Currenti, G.; Zuccarello, L.; Bonaccorso, A.; Sicali, A.
Abstract: Strainmeter and broadband seismic signals have been analyzed jointly with the aim of calibrating a borehole strainmeter at Etna volcano by using a seismo‐geodetic technique. Our results reveal a good coherence between the dynamic strains estimated from seismometer data and strains recorded by a dilatometer in a low‐frequency range [0.03–0.06 Hz] at the arrival of teleseismic waves. This significant coherence enabled estimating the calibration coefficient and making a comparison with calibration results derived from other methods. In particular, we verified that the proposed approach provides a calibration coefficient that matches the results obtained from the comparison of the recorded strain both with theoretical strain tides and with normal‐mode synthetic straingrams. The approach presented here has the advantage of exploiting recorded seismic data, avoiding the use of computed strain from theoretical models. Key Points: We propose a method introduced in seismology from geodesy for the "in situ" calibration of a borehole dilatometer from a broadband seismic array We found a good coherence in a low‐frequency band between the dilatometer and seismic strain, which enables calibrating the dilatometer The estimated calibration coefficient agrees with previous results obtained with other independent methods